Knowledge, Awareness, and perceived anxiety of human MonkeyPox among university students in Ras al Khaimah, United Arab of Emirates - Eman Abdelaziz Rashad Dabou; Fatma Magdi Ibrahim; Rose Ekama Ilesanmi (Elsevier, 2024)
Background: The students in university are part of the community with families. It is, therefore, essential to examine their awareness and knowledge regarding the mode of spread and their perceived anxiety level to plan and intervene as necessary. Aim: This study examined the awareness, knowledge and perceived anxiety regarding Monkeypox among the Medical and Health Sciences university students in Ras Al Khaimah, United Arab Emirates. Method: Across sectional design of 320 health profession university students was taken. Each participant provided a consent and completed an online validated questionnaire on awareness, and knowledge of monkeypox, as well as the Zung's self-rating anxiety questionnaire. Results: The students' mean age was comparable in the medical, nursing, dental, and pharmacy colleges (21.20 ± 2.8, 20.33 ± 2.4, 21.20 ± 2.5 and 21.12 ± 2.4). 78.4 % had poor knowledge levels, while only 3.1 % across the colleges demonstrated adequate knowledge. On level of anxiety, 26.6 % demonstrated mild to moderate anxiety. There was a statistically significant direct correlation between the students' awareness and knowledge (r = 0.433p < 0.05). Also, there was a weak inverse correlation between awareness and the level of anxiety (r = -0.102p > 0.05). There was a statistically significant association between the knowledge and year of education only in the dental college. Conclusion: MPOX-related knowledge was low among healthcare professional students in the study. We suggest that healthcare professional students should be exposed to epidemiology of tropical diseases even where the infection is not endemic in the regions. Recommendation: Students are at a vantage position to educate the public and families on risk prevention of infections of public health concern.